2013
DOI: 10.1016/j.jembe.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of three temperate coralline algae from contrasting habitats to near-future ocean acidification

Abstract: International audienceCoralline algae are major calcifiers of significant ecological importance in marine habitats but are among the most sensitive calcifying organisms to ocean acidification. The elevated pCO(2) effects were examined in three coralline algal species living in contrasting habitats from intertidal to subtidal zones on the north-western coast of Brittany, France: (i) Corallina elongata, a branched alga found in tidal rock pools, (ii) Lithophyllum incrustans, a crustose coralline alga from the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 77 publications
(60 reference statements)
7
93
1
2
Order By: Relevance
“…At local scale, coralline algae experiencing naturally diel pH variations are acclimatized to variable pH [29], and some temperate species found in habitats exposed to large pH changes (i.e. tidal pools) are more resistant to OA than species living in habitats characterized by more stable pH [28]. However, more pronounced negative effects of OA were found on the temperate coralline alga Arthrocardia corymbosa exposed to fluctuating pH [53], which suggests a limit to the capacity of coralline algae to acclimatize to OA.…”
Section: Discussionmentioning
confidence: 99%
“…At local scale, coralline algae experiencing naturally diel pH variations are acclimatized to variable pH [29], and some temperate species found in habitats exposed to large pH changes (i.e. tidal pools) are more resistant to OA than species living in habitats characterized by more stable pH [28]. However, more pronounced negative effects of OA were found on the temperate coralline alga Arthrocardia corymbosa exposed to fluctuating pH [53], which suggests a limit to the capacity of coralline algae to acclimatize to OA.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to predictions that calcified macroalgae will be impacted by future global change (Brodie et al, 2014). However, the effect of climate change is species-specific (Ries et al, 2009, ;Noisette et al, 2013) and some species have shown evidence of acclimation to future CO2 conditions (Ragazzola et al, 2013).…”
Section: Crouan and H Crouan Andmentioning
confidence: 99%
“…KUFFNER et al, 2008;SEMESI et al, 2009;NOISETTE et al, 2013;JOHNSON et al, 2014), but also in photosynthesis (e.g. ANTHONY et al, 2008;CARPENTER, 2012;COMEAU et al, 2012;JOHNSON et al, 2014;KATO et al, 2014;TAIT, 2014), cell wall thickness (RAGAZZOLA et al, 2012;RAGAZZOLA, 2014b), reproduction (CUMANI et al, 2010), recruitment , and survivorship (DIAZ-PULIDO et al, 2012).…”
Section: Global and Local Threatsmentioning
confidence: 99%
“…CARPENTER, 2012;MARTIN et al, 2013;NOISETTE et al, 2013;COMEAU et al, 2014) and light conditions (GAO;ZHENG, 2010;COMEAU et al, 2014), or local factors, such as nutrient concentration (RUSSELL et al, 2009;STENGEL et al, 2014). Besides a variety of studies investigating the OA response in coralline algae, only a few studies have been performed on the effect of the increase in seawater temperature and possible synergistic effects of ocean warming and acidification (see Figure 6B).…”
Section: Global and Local Threatsmentioning
confidence: 99%